Perceptions of Iranian High School EFL teachers and students toward teaching and learning reading skill - Karim Sadeghi,; Shiva Bidel Nikou, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
Following Chacón's (2005) contention that research on teachers' beliefs and their impact on teacher cognition has prevailed over the last four decades as an important filed of enquiry, this study attempted to find out how Iranian EFL teachers and students perceive the teaching status of reading skill in Iran’s high schools. The study was conducted in West Azerbaijan, Iran. One hundred and seventy one EFL high school teachers as well as 200 students were given separate questionnaires with both fixed-response and open-ended item. Qualitative and quantitative statistical techniques were used to analyse the data elicited. The findings revealed that both teachers and students agree that reading skill is highly paid attention to. The findings also revealed that books' shortcomings, lack of necessary equipment, and inappropriate assessment techniques are among the major problems that render high school EFL programs inadequate and undesirable in teaching reading. EFL teachers and policy makers are hoped to be in a better position to reflect on their current practices as a result of knowing the findings of this resear